Fifty Percent Reduction in Narcotic Use After Minimally Invasive Cardiac Surgery Using Liposomal Bupivacaine. Issue 6 (November 2019) - Castillo-Sang, Mario; Bartone, Cheryl; Palmer, Cassady; Truong, Vien T.; Kelly, Brian; Voeller, Rochus K.; Griffin, Jeffrey; Smith, Timothy; Raidt, Hilary; Answini, Geoffrey A.
Abstract : Objective: Minimally invasive cardiac surgery via a right minithoracotomy (RMT) is a common approach to different valve pathologies, tumor resection, and atrial septal defect (ASD) closure. We studied intraoperative field block using liposomal bupivacaine (LB) in these operations. Methods: Consecutive 171 minimally invasive RMTs (fourth intercostal space) were studied, and patients in cardiogenic or septic shock, intravenous drug abuse, and those re-explored were excluded ( n = 12). An early cohort was treated with standard postoperative analgesia while another underwent intraoperative field block with LB immediately after incision. We compared postoperative pain level, narcotic utilization (morphine milligram equivalent), and intensive care unit (ICU) and hospital length of stay. Results: The procedures included 48 isolated mitral valve replacements (MVR); 2 MVR with other procedures; 93 mitral valve repairs (MVRr); 9 MVRr with other procedures; 4 isolated tricuspid valve repairs; 2 myxoma resections; 1 ASD closure. There were 13 patients in the non-LB group and 146 patients in the LB group. Use of LB decreased mean postoperative narcotic utilization by 50% ( P = 0.003). The LB group had lower pain levels on postoperative day 1 ( P = 0.039), which continued through postoperative day 5 ( P = 0.030). We found no difference in ICU or hospital length of stay between groups. There were no complications from LB field block. Conclusions: LB field block decreases postoperative pain and narcotic utilization after cardiac surgery via a RMT, but it does not reduce length of stay. The technique is safe and should be considered in all patients undergoing RMT cardiac surgery.